2019
DOI: 10.3390/nu11051172
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Glycemic Index and Glycemic Load from Macronutrients to Accelerate Development of Foods and Beverages with Lower Glucose Responses

Abstract: Low glycemic index (GI) and/or low glycemic load (GL) are associated with decreased risks of type-2 diabetes and cardiovascular disease. It is therefore relevant to consider GI and GL in the early phases of the development of packaged foods and beverages. This paper proposes a model that predicts GI and GL from macronutrient composition, by quantifying both the impact of glycemic carbohydrates and the GI-lowering effects of nutrients such as proteins, fats and fibers. The precision of the model is illustrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
(39 reference statements)
0
17
0
3
Order By: Relevance
“…As for the results of GI and GL, lower values have contributed to the reduced risk of cardiovascular disease and diabetes (15). They investigated lots of kinds of breakfast, and reported that the average GI was 68.0 ± 9.2, and GL was 14.7 ± 3.1 g/30g weight (15).…”
Section: Discussionmentioning
confidence: 99%
“…As for the results of GI and GL, lower values have contributed to the reduced risk of cardiovascular disease and diabetes (15). They investigated lots of kinds of breakfast, and reported that the average GI was 68.0 ± 9.2, and GL was 14.7 ± 3.1 g/30g weight (15).…”
Section: Discussionmentioning
confidence: 99%
“…GI / GL was proposed by Jenkins et al, in which there are different carbohydrates for influencing potential metabolic responses with different glycemic responses (GR) [17]. The lower GI and GL have been beneficial for decreased risk of diabetes and cardiovascular disease (CVD) [18]. Among them, 42 breakfast cereals were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The factors included GI (in vivo versus predicted) and GL (g) for serving 30g (in vivo versus predicted). They showed that GI is 68 +/-9.2, GL (g) = 14.7 +/-3.1 g/30g, Sucrose = 20.1 +/-8.5g, Starch 51.1 +/-10.0 g [18].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which CGMs may be used to monitor diet is based on the fact that the evolution of blood glucose after a meal, also known as the postprandial glucose response (PPGR), depends on the macronutrients in the meal (e.g., carbohydrates, protein, fat, fiber). The major determinant of PPGRs is the amount of carbohydrates, but adding protein, fat, or fiber to a meal generally yields smaller spikes and lengthier responses [8,9]. This suggest that the shape of the PPGR can be used to recover the macronutrient composition of the meal.…”
Section: Introductionmentioning
confidence: 99%